Examining the impact of ceo power in the ownership-sustainability nexus: evidence from malaysian public listed firms - Norazlin, Ahmad (2022)
In response to the economic crisis, international organisations have encouraged the creation of sustainability standard. Excessive indebtedness and deficits have recently been identified as major risks for Public Listed Companies (PLCs). Therefore, this thesis examines three types of ownership shareholdings, namely government, family, and foreign ownership shareholdings and evaluate their respective impacts on the firm financial sustainability of publicly listed companies in Malaysia for the period of 2009-2019. Moreover, the 2007-2008 global financial crisis has highlighted the importance of Chief Executive Officer (CEO) power to achieve firm financial sustainability. The three general objectives of this thesis are to: (1) examine linear associations between ownership shareholdings (government, family and foreign) and firm financial sustainability; (2) investigate non-linear associations between ownership shareholdings (government, family and foreign) and firm financial sustainability; (3) evaluate the moderating role of powerful CEO оn thе association bеtween ownership shareholdings and firm financial sustainability. This thesis links resource dependency theory to the hypotheses concerning the linear effects of different ownership shareholdings on firm financial sustainability. Specifically, this thesis builds on Type II agency conflict to explain the non-linear effects. Furthermore, this study highlights the stewardship theory in explaining the moderating influence of powerful CEO on the relationship between ownership shareholdings and firm financial sustainability. The thesis sources of secondary data consist of all PLCs listed on the Main Board of Bursa Malaysia except for firms from finance, insurance, and real estate investment trust because their regulatory requirements differ from others. Sampling from the 2,830 firm-year observations and collected from annual reports for the year 2009-2019. The thesis concludes that: (1) government ownership shareholdings are not related to firm financial sustainability; (2) family ownership shareholding has a non-linear U-shaped association with firm financial sustainability; (3) foreign ownership is neither linearly nor non-linearly related to firm financial sustainability; (4) a powerful CEO is detrimental to a firm's financial sustainability; (5) CEO power moderates the nexus between government ownership shareholdings and firm financial sustainability; (6) at the family ownership shareholdings’ lowest level, CEOs serve as stewards to monitor the level of firm's financial sustainability; and (7) powerful CEO is incapable to moderate the association between foreign ownership shareholdings and firm financial sustainability. Overall, this thesis contributes to the growing body of knowledge in ownership shareholdings and CEO power, especially as the antecedents of firm financial sustainability in several dimensions, namely theoretical, methodological, and managerial perspective. Theoretically, this study supports the understanding of agency theory, stewardship theory, and corporate governance concept applied in the effects of CEO power in moderating the nexus between ownership shareholdings and firm financial sustainability. In terms of methodology, this study applies few different proxies and regression methods in examining the association between ownership shareholdings, CEO power and firm financial sustainability in Malaysian PLCs. Moreover, conceptually, this study provides direct evidence suggesting that the existence of a direct connection between CEO power and the firm financial sustainability. By understanding how ownership shareholdings and CEO power would affect the firm financial sustainability, policymakers or the Malaysia government itself can emphasize the PLCs to be more sustainable in the way that the business is handled.